2021
DOI: 10.3390/bios11090332
|View full text |Cite
|
Sign up to set email alerts
|

Use of PEDOT:PSS/Graphene/Nafion Composite in Biosensors Based on Acetic Acid Bacteria

Abstract: Immobilization of the biocomponent is one of the most important stages in the development of microbial biosensors. In this study, we examined the electrochemical properties of a novel PEDOT:PSS/graphene/Nafion composite used to immobilize Gluconobacter oxydans bacterial cells on the surface of a graphite screen-printed electrode. Bioelectrode responses to glucose in the presence of a redox mediator 2,6-dichlorophenolindophenol were studied. The presence of graphene in the composite reduced the negative effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Earlier, we proposed a method for the immobilization of acetic acid bacteria on graphite screen-printed electrodes using a PEDOT:PSS/graphene/Nafion composite. These electrodes were used as part of a glucose biosensor [ 29 ]. In this work, the developed composite was used to create a microbial fuel cell based on Gluconobacter oxydans bacteria for wastewater treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, we proposed a method for the immobilization of acetic acid bacteria on graphite screen-printed electrodes using a PEDOT:PSS/graphene/Nafion composite. These electrodes were used as part of a glucose biosensor [ 29 ]. In this work, the developed composite was used to create a microbial fuel cell based on Gluconobacter oxydans bacteria for wastewater treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, G. oxydans cells are a promising candidate for the creation of effective MFCs because their cell membrane contains pyrroloquinolinquinone (PQQ)-dependent dehydrogenases, which are capable of efficiently oxidizing a number of compounds [ 28 ]. Our previous work has developed a new conductive composite based on PEDOT:PSS, graphene and Nafion, which we used to effectively immobilize G. oxydans bacteria on the surface of screen-printed graphite electrodes [ 29 ]. It has been shown that the use of PEDOT:PSS in combination with graphene improves the analytical characteristics of a microbial biosensor; the use of graphene neutralizes the negative action of PEDOT:PSS on bacterial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The second component, the transducer helps in recording the interaction between the biological part with the analyte in the form of signals such as electrochemical, thermal, or optical. 67 The conducting polymers, 26 carbon-based materials such as CNT, 68 graphene, 69,70 and metal nanoparticles 71 are used as electrodes in biosensing applications. The flexibility, solution processability, and low cost are the advantages of conducting polymers materials.…”
Section: Properties Required For Biosensorsmentioning
confidence: 99%
“…The electrically conductive properties of many polymers are increased by the addition of nanomaterials, e.g., carbon nanotubes [ 62 , 63 ], graphene [ 64 ], etc. It should be noted that the use of various nanomaterials to improve the characteristics of amperometric biosensors is a certain trend, which is also used in the creation of mediator BOD biosensors [ 30 , 51 , 57 ].…”
Section: Types Of Transducersmentioning
confidence: 99%